Similarities and differences between families who have frequent and infrequent family meals: A qualitative investigation of low-income and minority households. (April 2018) - Berge, Jerica M.; Draxten, Michelle; Trofholz, Amanda; Hanson-Bradley, Carrie; Justesen, Kathryn; Slattengren, Andrew
Abstract: Introduction: Numerous quantitative studies have examined the association between family meal frequency and child/adolescent weight and weight-related behaviors. However, limited qualitative research has been conducted to identify mealtime characteristics (e.g., child behavior during meals, rules/expectations, family dynamics) that occur during family meals that may explain why some families engage in frequent family meals and others do not. This is particularly important within racially/ethnically diverse households, as these demographic groups are at higher risk for weight-related problems. The current study aimed to identify similarities and differences in mealtime characteristics between households that have frequent and infrequent family meals within a low-income and minority population. Methods: This qualitative study included 118 parents who participated in Family Meals, LIVE!, a mixed-methods, cross-sectional study. Parents (90% female; mean age = 35) were racially/ethnically diverse (62% African American, 19% White, 4% Native American, 4% Asian, 11% Mixed/Other) and from low-income (73% < $35, 000/yr.) households. Data were analyzed using inductive content analysis. Results: Results indicated some similar mealtime characteristics (i.e., picky eating, involving family members in meal preparation) between households having frequent and infrequent family meals. Additionally, several differences in mealtime characteristics were identified between households having frequent (i.e., importance of family meals, flexibility in the definition of family meals, family meal rules, no pressure-to-eat feeding practices) versus infrequent family meals (i.e., pressure-to-eat parent feeding practices, family meals are dinner meals only, and difficult meal time behaviors). Discussion: Study findings may be useful for developing intervention targets for low-income and racially/ethnically diverse households so more families can benefit from the protective nature of family meals. Highlights: Families having frequent family meals had flexible definitions of family meals. Families having frequent family meals had rules/expectations at family meals. Families having frequent family meals thought family meals were important. Families having infrequent family meals had more controlling feeding practices. Families having infrequent family meals had difficult child behaviors at meals.